2009
DOI: 10.1038/nature08489
|View full text |Cite
|
Sign up to set email alerts
|

Mutational evolution in a lobular breast tumour profiled at single nucleotide resolution

Abstract: Recent advances in next generation sequencing have made it possible to precisely characterize all somatic coding mutations that occur during the development and progression of individual cancers. Here we used these approaches to sequence the genomes (>43-fold coverage) and transcriptomes of an oestrogen-receptor-alpha-positive metastatic lobular breast cancer at depth. We found 32 somatic non-synonymous coding mutations present in the metastasis, and measured the frequency of these somatic mutations in DNA fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
735
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 983 publications
(788 citation statements)
references
References 19 publications
32
735
1
3
Order By: Relevance
“…In addition, the imbalances of SNP allele frequencies were used to correctly predict an LOH on chromosome 3 in only a subset of the tumour samples. Recent studies found genomic heterogeneity in breast cancer 10,24 , pancreatic cancer 25,26 , and B-cell chronic lymphocytic leukemia 9 , as well as mosaic amplifications of tyrosine kinase receptor genes in glioblastoma 27 . Together, these findings provide compelling evidence for clonal evolution as a general mechanism in cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the imbalances of SNP allele frequencies were used to correctly predict an LOH on chromosome 3 in only a subset of the tumour samples. Recent studies found genomic heterogeneity in breast cancer 10,24 , pancreatic cancer 25,26 , and B-cell chronic lymphocytic leukemia 9 , as well as mosaic amplifications of tyrosine kinase receptor genes in glioblastoma 27 . Together, these findings provide compelling evidence for clonal evolution as a general mechanism in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…They enable direct sequencing of mixed samples, such as virus populations 6,7 , bacterial communities 8 , tumours [9][10][11] and pooled samples 12,13 , and the reconstruction of their genomic composition. However, single-nucleotide errors resulting from target enrichment, library preparation and base calling are frequent on all current sequencing platforms 5 , and they are difficult to separate from true lowfrequency single-nucleotide variants (SNVs).…”
mentioning
confidence: 99%
“…500 ng was used for Illumina library construction as previously described. 48 The library then underwent a selected gene capture step consisting of 15 genes that included BRCA1 and BRCA2 using cDNA as the capture probe. The select gene capture data were first aligned to the whole genome using the BWA (LD09) 49 aligner, and the alignment results were converted to bam files (LHW þ 09).…”
Section: Brca1 and Brca2 Somatic Mutation Testingmentioning
confidence: 99%
“…Interestingly, recent genomic profiling studies 24, 25, 26, 27, 28, 29, 30, 31 suggested a substantial degree of intra‐ and inter‐tumour heterogeneity fuelling selection processes during evolution of breast cancer 32, 33, which may complicate prognostication as well as prediction and impede cancer precision medicine approaches 34. In this context, it is worth recalling that just as the molecular phenotype, the morphological phenotype of the tumour, including tumour grade and tumour size is essentially a result of accumulated genetic aberrations over time, thereby reflecting tumour evolution at the phenotypic level.…”
Section: Introductionmentioning
confidence: 99%